Anslag på bankenes tap på utlån til ikke-finansielle foretak; Estimates of banks' losses on loans to the corporate sector - Ida Nervik Hjelseth; Elif Arbatli; Haakon Solheim; Bjørn Helge Vatne (Norges Bank, 2020)
– Loans to non-financial enterprises are the main source of banks' losses. Analyses of banks' losses on corporate loans are therefore important in the assessment of financial stability. This paper presents Norges Bank's framework for estimating losses on corporate loans built up from microdata for each firm and loan in each bank. Losses are estimated using a stepwise process. First, we estimate revenue developments at industry level and simulate the effect on firms' future financial statements. This is then used to project firms' bankruptcy probabilities using Norges Bank's bankruptcy probability model (KOSMO). Finally, the bankruptcy probabilities are linked to data on banks' exposures and credit losses are estimated. The estimates will be included in Norges Bank's assessment of vulnerabilities and risks in the Norwegian banking system. In addition to being included in a general risk assessment, the framework can be used in stress testing and in the assessment of new areas of risk, such as climate risk.
hdl:11250/2711091
Keywords: 330; credit risk; bankruptcy probability; credit losses; bank losses; Kreditgeschäft; Unternehmensfinanzierung; Insolvenz; Bankrisiko; Norwegen